Timing of elective tracheotomy and duration of mechanical ventilation amongst patients admitted to intensive care with severe COVID-19: a multicentre prospective cohort study - Sánchez Barrueco, Álvaro; Prats Uribe,Albert; Tobed, Marc; Villacampa Auba, José Miguel; Agüero, Adriana; García Bastida, Clara; Tato, José Ignacio; Rodrigáñez, Laura; Duque Holguera, Victoria; Hernández García, Estefanía; Poletti, Daniel; Simonetti, Gabriela; et al. (My University, 2021)
Background: The COVID-19 pandemic has strained intensive care unit (ICU) resources. Tracheotomy is the most frequent surgery performed on ICU patients and can affect the duration of ICU care. We studied the association between when tracheotomy occurs and weaning from mechanical ventilation, mortality, and intraoperative and postoperative complications. Methods: Multicentre prospective cohort including all COVID-19 patients admitted to ICUs in 36 hospitals in Spain who received invasive mechanical ventilation and tracheotomy between 11 March and 20 July 2020. We used a target emulation trial framework to study the causal effects of early (7 to 10 days post-intubation) versus late (>10 days) tracheotomy on time from tracheotomy to weaning, postoperative mortality, and tracheotomy complications. Cause-specific Cox models were used for the first two outcomes and Poisson regression for the third, all adjusted for potential confounders. Findings: We included 696 patients, of whom 142 (20·4%) received early tracheotomy. Using late tracheotomy as the reference group, multivariable cause-specific analysis showed that early tracheotomy was associated with faster post-tracheotomy weaning (fully adjusted hazard ratio (HR) [95% confidence interval (CI)]: 1·31 [1·02 to 1·81]) without differences in mortality (fully adjusted HR [95% CI]: 0·91 [0·56 to 1·47]) or intraoperative or postoperative complications (adjusted rate ratio [95% CI]: 0·21 [0·03 to 1·57] and 1·49 [0·99 to 2·24], respectively). Interpretation: Early tracheotomy reduced post-tracheotomy weaning time, resulting in fewer mechanical ventilation days and shorter ICU stays, without changing complication or mortality rates. These results support early tracheotomy for COVID-19 patients when clinically indicated. Funding: Supported by the NIHR, FAME, and MRC. Key words: SARS-CoV-2, Intensive care, Respiratory failure, weaning, complications.